Enhancing the Textural Properties of Tibetan Pig Sausages via Zanthoxylum bungeanum Aqueous Extract: Polyphenol-Mediated Quality Improvements - Jingjing Huang; Haiqiu Wei; Zhang Luo; Liang Li; Zhendong Liu; Ningning Xie (Foods)
The mechanistic effects of Zanthoxylum bungeanum on the textural properties of Tibetan pig sausages remain inadequately elucidated. We conducted a dose–response analysis using Z. bungeanum aqueous extraction (ZBAE) containing 36.97 mg GAE/g polyphenols, applied at concentrations from 0.125% to 1.20% in the meat paste. Optimal textural enhancement was achieved at 0.25% ZBAE, as proved by significantly improving water holding capacity (1.77% increase), hardness (139.87% increase), and gel strength (46.04% increase) relative to the control group (p < 0.05). Specifically, this concentration: (i) promoted protein molecular rearrangement of by enhancing hydrophobic interactions (33.33% increase) and hydrogen bonding (287.99% increase); (ii) induced conformational transitions from α-helix (42.62% decrease) to β-sheet formations (21.11% increase); and (iii) generated a homogeneous three-dimensional protein network characterized by a fractal dimension of 2.769 ± 0.006 and a porosity of 38.350 ± 0.333%. The addition of natural polyphenols from Z. bungeanum may optimize the textural quality of processed meat products.